PEMBELAJARAN DALAM PERSPEKTIF KREATIVITAS GURU DALAM PEMANFAATAN MEDIA PEMBELAJARAN - Ramli Abdullah (UIN AR-RANIRY, 2016)
Learning will work well without using media appropriate to the material to be taught, because apart from being an intermediary media is also useful to overcome the limitations of space, time, and power the senses, such as an object that is too large can be replaced with reality, image, or movie frame , In use in the learning process, the teacher must know and master as well as capable of using media in teaching and learning. This capability is an imaginative activity that result is the formation of a combination of information obtained from previous experiences into new, meaningful and useful. So therefore, the creativity of teachers in the use of instructional media can be concluded, namely: (1) The creativity of teachers in the use of instructional media in learning a subject usually, only teachers use media such as books, whiteboard and markers. The success of the learning process depends on the competence of teachers in mastering the material or subject matter. Schools seek help improve the facilities and means associated with school education in one facility and related instructional media to increase student achievement and quality of education in schools.